Assessment Ketersediaan Beras Pada 34 Provinsi di Indonesia - Marzani, Yura; Juliannisa, Indri Arrafi (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Indonesia is an agricultural country, which means that the agricultural sector plays an important role in supporting the national economy. The agricultural sector has a very significant contribution to achieving the goals of the two Sustainable Development Goals (SDGs) programs, namely no hunger, achieving food security, improving nutrition and encouraging sustainable agricultural cultivation. Food crops are included in the main products of the agricultural sector in Indonesia. One of the food crops that has an important role as a supporter of food security is the rice commodity. In this study, Indonesia became the object of research using data for 2020 from 34 provinces in Indonesia. In examining the condition of rice availability from 34 provinces in Indonesia, this study used the Multi Criteria Decision Making